Migrants' primary care utilisation before and during the COVID-19 pandemic in England: An interrupted time series analysis - Claire X. Zhang; Yamina Boukari; Neha Pathak; Rohini Mathur; Srinivasa Vittal Katikireddi; Parth Patel; Ines Campos-Matos; Dan Lewer; Vincent Nguyen; Greg C.G. Hugenholtz; Rachel Burns; Amy Mulick; et al. (Elsevier, 2022)
Summary: Background: How international migrants access and use primary care in England is poorly understood. We aimed to compare primary care consultation rates between international migrants and non-migrants in England before and during the COVID-19 pandemic (2015-2020). Methods: Using data from the Clinical Practice Research Datalink (CPRD) GOLD, we identified migrants using country-of-birth, visa-status or other codes indicating international migration. We linked CPRD to Office for National Statistics deprivation data and ran a controlled interrupted time series (ITS) using negative binomial regression to compare rates before and during the pandemic. Findings: In 262,644 individuals, pre-pandemic consultation rates per person-year were 4.35 (4.34-4.36) for migrants and 4.60 (4.59-4.60) for non-migrants (RR:0.94 [0.92-0.96]). Between 29 March and 26 December 2020, rates reduced to 3.54 (3.52-3.57) for migrants and 4.2 (4.17-4.23) for non-migrants (RR:0.84 [0.8-0.88]). The first year of the pandemic was associated with a widening of the gap in consultation rates between migrants and non-migrants to 0.89 (95% CI 0.84-0.94) times the ratio before the pandemic. This widening in ratios was greater for children, individuals whose first language was not English, and individuals of White British, White non-British and Black/African/Caribbean/Black British ethnicities. It was also greater in the case of telephone consultations, particularly in London. Interpretation: Migrants were less likely to use primary care than non-migrants before the pandemic and the first year of the pandemic exacerbated this difference. As GP practices retain remote and hybrid models of service delivery, they must improve services and ensure primary care is accessible and responsive to migrants' healthcare needs. Funding: This study was funded by the Medical Research Council (MC_PC 19070 and MR/V028375/1) and a Wellcome Clinical Research Career Development Fellowship (206602).